RF Energy Harvesting for Ubiquitous, Zero Power Wireless Sensors - Warda Saeed; Nosherwan Shoaib; Hammad M. Cheema; Muhammad U. Khan (International Journal of Antennas and Propagation)
This paper presents a review of wireless power transfer (WPT) followed by a comparison between ambient energy sources and an overview of different components of rectennas that are used for RF energy harvesting. Being less costly and environment friendly, rectennas are used to provide potentially inexhaustible energy for powering up low power sensors and portable devices that are installed in inaccessible areas where frequent battery replacement is difficult, if not impossible. The current challenges in rectenna design and a detailed comparison of state-of-the-art rectennas are also presented.